Lessons Learned From Delivering Imara, an HIV/STI Risk Reduction Intervention for African American Girls in Juvenile Detention. Issue 1 (January 2016) - Davis, Teaniese L.; Boyce, Lorin S.; Rose, Eve; Swartzendruber, Andrea; DiClemente, Ralph; Gelaude, Deborah; Fasula, Amy M.; Carry, Monique
A critical need exists for efficacious interventions to reduce sexual risk and sexually transmitted infections (STIs) among African American girls in juvenile detention. Adapting evidence-based interventions is one strategy for developing interventions that might protect detained African American girls from adverse sexual health outcomes. To support development and implementation of evidence-based HIV/STI prevention interventions for this population, this qualitative study describes lessons learned from delivering Imara, an adapted HIV/STI prevention intervention for detained African American girls. Program implementation includes one-on-one sessions in the detention facility that offer logistical advantages; provide intervention contact inside the facility, soon after release, and frequently thereafter; address STI treatment for girls and their sexual partners; tailor intervention content based on individual risk and learning needs; and identify and acknowledge girls' competing priorities. These lessons are discussed in the context of challenges encountered and solutions for addressing the challenges, and in terms of the structure and content of the intervention. The lessons learned from delivering Imara exemplify the continuous process of adapting an existing intervention for a new population and setting.